Pengembangan website ujian tes TOEFL pada Lembaga Kursus “Plug-in” - Wijaya, Arya Bima; Widayati, Yohana Tri; Prakoso, Satrio Agung (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2025)
The TOEFL test is an international standard for measuring English language ability. This research developed a web-based TOEFL examination system at the “Plug-in” Training Institute using the Scrum method to address the shortcomings of the old system, such as audio control, score accuracy, and insufficient detail in recording results. The data were collected through observation, interviews, and literature study. Scrum was applied in three sprints that focused on the listening section navigation, score calculation, and answer logging. Features for single audio playback, a timer, automatic score calculation, and a detailed results display were successfully implemented. Testing showed the system to be stable and accurate according to TOEFL standards. This system improves efficiency, fairness, and user experience in digital TOEFL examinations. Suggestions for development include broader testing, UI/UX optimization, a data export feature, and more detailed answer logging for analysis.